Defence Policy-Making: A Close-Up View, 1950-1980 A Personal Memoir - Arthur Tange, Sir (ANU Press, 2008)
Sir Arthur Tange was perhaps the most powerful Secretary of the Australian Defence Department and one of the most powerful of the great 'mandarins' who dominated the Commonwealth Public Service between the 1940s and the 1970s. His strong, and often decisive, influence on both administration and policy was exerted by virtue of his intellectual capacity, his administrative ability and the sheer force of his personality. Controversies from his time in Defence, including those associated with 'the Tange report' and 'the Tange reforms', echo to this day, and it is still easy to identify both staunch admirers and vitriolic critics in defence and public service circles. Tange wrote this account in his last years. It is a memoir - based largely on memory supplemented by limited reference to documentary material - that focuses upon his career after he came to Defence in 1970. It records his own account of his part in those administrative reforms and policy shifts, as well as his involvement-or non-involvement or alleged involvement-in several of the political crises of the 1970s, including the downfall of John Gorton as Prime Minister and the dismissal of the Whitlam Government.